2002
DOI: 10.1002/1521-3757(20020916)114:18<3639::aid-ange3639>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Dedicated to Professor Dieter Fenske on the occasion of his 60th birthdayThe replication of nanoscale structures by a direct templating process has been used in recent years in several creative ways for the synthesis of carbon replicas of zeolites [1] or ordered mesoporous carbons, such as CMK-1 [2] or SNU-1. [3] Such processes rely on the fact that an ordered pore system, provided by the zeolite or ordered mesoporous silica, can be filled with a carbon precursor which is pyrolyzed and the silica leached w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 1 publication
0
18
0
5
Order By: Relevance
“…[23][24][25][26][27] While extension to other compositions has been attempted again and again over the last 15 years,t his has not been successful so far. In the following,w ed escribe as urface-casting method for the synthesis of crystalline zirconias with very high surface areas,a nd in selected cases in form of nanotube arrays (surface cast oxide,S CO), which can be extended also to other oxides.T he process relies on as ilanol group-rich mesoporous silica as hard template,w ith as urface functionalization step being crucial for the formation of the thin oxide coating.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] While extension to other compositions has been attempted again and again over the last 15 years,t his has not been successful so far. In the following,w ed escribe as urface-casting method for the synthesis of crystalline zirconias with very high surface areas,a nd in selected cases in form of nanotube arrays (surface cast oxide,S CO), which can be extended also to other oxides.T he process relies on as ilanol group-rich mesoporous silica as hard template,w ith as urface functionalization step being crucial for the formation of the thin oxide coating.…”
mentioning
confidence: 99%
“…[12] Nanocasting is an alternative method for preparing mesoporous materials that are difficult to synthesize with the conventional soft templating method. [19] Following the work by Lu et al, [20] several ordered mesoporous materials, including MgO, [21] boron nitride, [22] g-Al 2 O 3 , [23] aluminosilicate, [24] CuO, [25] and ZnO, [26] were nanocast by using ordered mesoporous carbon CMK-3 as a matrix.The control of interfacial properties through tunable surface functionalities is essential in the development of functional mesoporous materials. [19] Following the work by Lu et al, [20] several ordered mesoporous materials, including MgO, [21] boron nitride, [22] g-Al 2 O 3 , [23] aluminosilicate, [24] CuO, [25] and ZnO, [26] were nanocast by using ordered mesoporous carbon CMK-3 as a matrix.…”
mentioning
confidence: 99%
“…[13] This hard templating approach has been applied to prepare different kinds of metal oxides, such as CoO, [14] Co 3 O 4 , [15] Mn 3 O 4 , [16] Fe 2 O 3 , [17] Fe 3 O 4 , [18] and NiO. [19] Following the work by Lu et al, [20] several ordered mesoporous materials, including MgO, [21] boron nitride, [22] g-Al 2 O 3 , [23] aluminosilicate, [24] CuO, [25] and ZnO, [26] were nanocast by using ordered mesoporous carbon CMK-3 as a matrix.The control of interfacial properties through tunable surface functionalities is essential in the development of functional mesoporous materials. To the best of our knowledge, no versatile method for preparation of fluorine-doped mesoporous metal oxides has been reported previously.…”
mentioning
confidence: 99%
“…[83] The resulting silica, denoted as NCS-1, had the same morphology and pore structure as the SBA-15 material used as a mold for CMK-3 (shown in Figure 15). As proof of principle, it was shown that replication of CMK-3 with silica is possible by infiltration of tetraethoxysilane (TEOS) into the pores of CMK-3, followed by hydrolysis and condensation of the silica, catalyzed with a mineral acid.…”
Section: Nanocastingmentioning
confidence: 99%
“…As proof of principle, it was shown that replication of CMK-3 with silica is possible by infiltration of tetraethoxysilane (TEOS) into the pores of CMK-3, followed by hydrolysis and condensation of the silica, catalyzed with a mineral acid. [83] The resulting silica, denoted as NCS-1, had the same morphology and pore structure as the SBA-15 material used as a mold for CMK-3 (shown in Figure 15). However, NCS-1 has somewhat smaller pore diameters, due to shrinking during the successive replication processes.…”
Section: Nanocastingmentioning
confidence: 99%